2016
DOI: 10.2308/ajpt-51514
|View full text |Cite
|
Sign up to set email alerts
|

Current Practices and Challenges in Auditing Fair Value Measurements and Complex Estimates: Implications for Auditing Standards and the Academy

Abstract: SUMMARY:Auditing fair value measurements and other complex estimates (hereafter, FVMs) has received significant attention from regulators, practitioners, and researchers. Using a survey, we gather data from audit partners with FVM expertise to gain further insights in areas that have not been fully explored in the previous literature. Specifically, we extend the literature by providing a deeper understanding of the following areas: auditors' use of different substantive approaches to test higher-risk FVMs, aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 25 publications
6
94
1
1
Order By: Relevance
“…Our results have important implications for practitioners, researchers, regulators, standard setters, and inspectors worldwide as collective efforts continue to reduce reported deficiencies associated with audits of FVMs (e.g., IFIAR , ; PCAOB , ). Our findings suggest that the normative theory applied in most previous studies is necessary, but not sufficient to explain the level and extent of recurring deficiencies in audits of FVMs (Griffith, Hammersley, and Kadous ; Glover et al ). We find evidence of differences of opinion between auditor and inspector experts and the presence of the FVM gap.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Our results have important implications for practitioners, researchers, regulators, standard setters, and inspectors worldwide as collective efforts continue to reduce reported deficiencies associated with audits of FVMs (e.g., IFIAR , ; PCAOB , ). Our findings suggest that the normative theory applied in most previous studies is necessary, but not sufficient to explain the level and extent of recurring deficiencies in audits of FVMs (Griffith, Hammersley, and Kadous ; Glover et al ). We find evidence of differences of opinion between auditor and inspector experts and the presence of the FVM gap.…”
Section: Introductionmentioning
confidence: 58%
“…Results presented in the current study are part of a larger survey, including results reported in Glover et al ().…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In this setting, adding red marbles is analogous to upward distortion of a financial report, which, if left uncorrected by the auditor, increases the likelihood of audit failure and negative consequences for the auditor (e.g., Palmrose [], Chaney and Philipich [], Glover, Taylor, and Wu []). For simplicity, there is no literal value communicated by the reporter to the auditor, as the reporter's only action is to add red marbles.…”
Section: Methods and Designmentioning
confidence: 99%
“…Previous research suggests that a lack of guidance from auditing standards on the use of experts (Griffith, 2013), a lack of availability of verifiable data and proprietary models used by experts in fair value measurements (Glover, Taylor, & Wu, 2017), and a coercive enforcement style adopted by the regulator (Dowling, Knechel, & Moroney, 2015) are contributing toward tension between auditors and regulators. Second, auditors perceive the ASIC's findings of inadequate audit evidence to stem from a lack of sufficient audit documentation and not necessarily from a lack of audit effort.…”
mentioning
confidence: 99%